A national language policy for Zimbabwe in the twenty- first century: myth or reality?: Paper presented at a Conference in Botswana - Nhongo, Raphael (Midalands State University, 2014)
The thrust of the paper is on the activities that have taken place in Zimbabwe concerning the formulation of a plausible national language policy. The paper looks at how the current Zimbabwe’s language situation affects its social, economic, political and educational development. The paper begins by tracing the history of language activities in Zimbabwe from the pre-colonial era and linking such activities with those that are taking place currently and how such activities have had an influence in development. The education act which is the only official policy document concerning language in Zimbabwe is scrutinized by focusing on how it is being implemented and practiced. Major focus concerning the education act is paid to the Matabeleland region since this is where there are a variety of languages that exist where the dominant language in education is Ndebele and when such languages mutually unintelligible with Ndebele. On the practice and implementation of the Zimbabwe’s education act, the key players in education such as the responsible ministers and principal directors, education officers and teachers are going to be interviewed. The paper problematizes the idea of language and economic development as to which one between language development and economic development should come first. The paper concludes by scrutinizing the link between multilingualism, politics of the day and meaningful development.